Stress Overload and DNA Methylation in African American Women in the Intergenerational Impact of Genetic and Psychological Factors on Blood Pressure Study - Jolaade Kalinowski; Yunfeng Huang; Martin A Rivas; Veronica Barcelona; Michelle L Wright; Cindy Crusto; Tanya Spruill; Yan V Sun; Jacquelyn Y Taylor (SAGE Journals, 2022)
Introduction:
Experiencing psychosocial stress is associated with poor health outcomes such as hypertension and obesity, which are risk factors for developing cardiovascular disease. African American women experience disproportionate risk for cardiovascular disease including exposure to high levels of psychosocial stress. We hypothesized that psychosocial stress, such as perceived stress overload, may influence epigenetic marks, specifically DNA methylation (DNAm), that contribute to increased risk for cardiovascular disease in African American women.
Methods:
We conducted an epigenome-wide study evaluating the relationship of psychosocial stress and DNAm among African American mothers from the Intergenerational Impact of Genetic and Psychological Factors on Blood Pressure (InterGEN) cohort. Linear mixed effects models were used to explore the epigenome-wide associations with the Stress Overload Scale (SOS), which examines self-reported past-week stress, event load and personal vulnerability.
Results:
In total, n = 228 participants were included in our analysis. After adjusting for known epigenetic confounders, we did not identify any DNAm sites associated with maternal report of stress measured by SOS after controlling for multiple comparisons. Several of the top differentially methylated CpG sites related to SOS score (P < 1 × 10−5), mapped to genes of unknown significance for hypertension or heart disease, namely, PXDNL and C22orf42.
Conclusions:
This study provides foundational knowledge for future studies examining epigenetic associations with stress and other psychosocial measures in African Americans, a key area for growth in epigenetics. Future studies including larger sample sizes and replication data are warranted.
Keywords: Cell Biology